New and poorly known species of Bowie Jäger, 2022 (Araneae: Ctenidae) from Southeast Asia - Omelko, Mikhail M.; Fomichev, Alexander A. (Zootaxa, 2024)
Three new species, B. catopuma sp. nov. (♀) (Borneo, Malaysia), B. musang sp. nov. (♂♀) and B. tangalunga sp. nov. (♂) (both from Mindanao, Philippines), are described. Species of shakeit group are recorded outside of Borneo for the first time (Philippines). The females of Bowie neukoeln Jäger, 2022 and Bowie shakeit Jäger, 2022, and the male of B. hosei (F.O. Pickard-Cambridge, 1897) are redescribed. Detailed descriptions, digital photographs and a distributional map are provided.